Characterization of polyethylene glycol plasticized carboxymethyl cellulose-ammonium fluoride solid biopolymer electrolytes - M. A. Ramlli; M. A. Maksud; M. I. N. Isa (American Institute of Physics, 2024)
Indexed by SCOPUS